Adaptive position control of a cart moved by a DC motor using integral controller tuned by Jaya optimization with Balloon effect. (October 2020) - Mohamed, Tarek Hassan; Alamin, Mohamed Abdelhamid Mohamed; Hassan, Ammar M.
Highlights: New modification for Jaya optimization using Balloon effect has been introduced. Balloon effect is increasing the sensitivity of the Jaya to system problems. Proposed technique has been applied to adaptive position controller of a DC motor. Simulation and experimental tests supported the efficiency of the proposed method. Abstract: This study suggests an adaptive linear position control of a car moved by an armature-controlled DC motor. In this study, Jaya optimization algorithm supported by Balloon effect (BE) is used to tune the parameters of the controller of the car position. BE is introduced to improve response of the classical Jaya algorithm in face of the external disturbance and system parameters changes. In the suggested technique, an objective function (OF) of the modified Jaya depends on the updated values of the controller gains and identified value of the motor open loop transfer function. System with the suggested controller has been evaluated in case of step load disturbance and motor parameters changes. Simulation and experimental results supported that suggested adaptive controller using modified Jaya improved the total system performance at moments of load disturbance and uncertainties of system parameters. Graphical abstract: Block diagram of an adaptive control system of a cart moved by a DC motor using Jaya + BE Image, graphical abstract